TRADUÇÃO DE CONTOS DE MOREIRA CAMPOS PARA O FRANCÊS: ESBOÇO DE UMA PAISAGEM LITERÁRIA - Kunz, Martine (Revista de Letras, 2016)
TRADUÇÃO DE CONTOS DE MOREIRA CAMPOS PARA O FRANCÊS: ESBOÇO DE UMA PAISAGEM LITERÁRIA